# Solve for y -6/5=2/3y -65=23y
Rewrite the equation as 23y=-65.
23y=-65
Multiply both sides of the equation by 32.
32⋅23⋅y=32⋅(-65)
Simplify both sides of the equation.
Simplify 32⋅23⋅y.
Cancel the common factor of 3.
Cancel the common factor.
32⋅23⋅y=32⋅(-65)
Rewrite the expression.
12⋅2⋅y=32⋅(-65)
12⋅2⋅y=32⋅(-65)
Cancel the common factor of 2.
Cancel the common factor.
12⋅2⋅y=32⋅(-65)
Rewrite the expression.
1⋅y=32⋅(-65)
1⋅y=32⋅(-65)
Multiply y by 1.
y=32⋅(-65)
y=32⋅(-65)
Simplify 32⋅(-65).
Cancel the common factor of 2.
Move the leading negative in -65 into the numerator.
y=32⋅-65
Factor 2 out of -6.
y=32⋅2(-3)5
Cancel the common factor.
y=32⋅2⋅-35
Rewrite the expression.
y=3⋅-35
y=3⋅-35
Combine 3 and -35.
y=3⋅-35
Simplify the expression.
Multiply 3 by -3.
y=-95
Move the negative in front of the fraction.
y=-95
y=-95
y=-95
y=-95
The result can be shown in multiple forms.
Exact Form:
y=-95
Decimal Form:
y=-1.8
Mixed Number Form:
y=-145
Solve for y -6/5=2/3y

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top